Table of Content - - (Arab Journal for Sciences and Research Publishing, 2024)
Table of Content: 1. The field of intelligence study in academic institutions: A comparative analytical study of American and British intelligence studies Dr. Mohamed Elzin Mohamed Ahmed Ibrahim 2. The effectiveness of the Madrasati platform according to the Needham constructivist model in increasing achievement of second-year intermediate female students in the TIMSS tests (algebra field) and the teacher’s point of view Mariam Farhan Alfifi, Ghada Owaid Awad Al-Sahli 3. Social support programs: its effects on girls schooling and reducing dropping out of school in the northeast middle Atlas – Morocco Mr. Abdelilah El-Alami, Prof. Dr. Jaouad El-Bazoui, Prof. Dr. Abdelouahed Bouberria 4. The growing influence of China in the Middle East and its implications for US relations Dr. Khaldoun Abdul Samad 5. Balfour’s Legacy: Britain, Zionism, and the Controversial Path to Israel’s Establishment Ali Mohammed Qader 6. The Impact of Organizational Citizenship on Job Performance of Employees in the Private Automotive Sector in Saudi Arabia in light of 2030’s vision Mr. Ahmed Farouk Ali, Dr. Elsayed Eid, Dr. Heba Alhadad